ChemInform Abstract: Chemoselective Reductive Nucleophilic Addition to Tertiary Amides, Secondary Amides, and N‐Methoxyamides. Issue 22 (15th May 2015) - Nakajima, Minami; Oda, Yukiko; Wada, Takamasa; Minamikawa, Ryo; Shirokane, Kenji; Sato, Takaaki; Chida, Noritaka
Abstract: The title transformation consists of (i) reduction of the amide carbonyl group, (ii) formation of an iminium ion with an acid, and (iii) C—C bond formation with a mild nucleophile.